Effectiveness of Augmentative Biological Control of Streptomyces griseorubens UAE2 Depends on 1-Aminocyclopropane-1-Carboxylic Acid Deaminase Activity against Neoscytalidium dimidiatum - Bader M. Al Hamad (MDPI AG, 2021)
To manage stem canker disease on royal poinciana, actinobacterial isolates were used as biological control agents (BCAs) based on their strong in vitro inhibitory effects against Neoscytalidiumdimidiatum. Streptomyces griseorubens UAE2 and Streptomyces wuyuanensis UAE1 had the ability to produce antifungal compounds and cell-wall-degrading enzymes (CWDEs). Only S. griseorubens, however, restored the activity of 1-aminocyclopropane-1-carboxylate (ACC) deaminase (ACCD). In vivo apple fruit bioassay showed that lesion development was successfully constrained by either isolates on fruits inoculated with N. dimidiatum. In our greenhouse and container nursery experiments, S. griseorubens showed almost complete suppression of disease symptoms. This was evident when the preventive treatment of S. griseorubens significantly (p < 0.05) reduced the numbers of conidia of N. dimidiatum and defoliated leaves of royal poinciana seedlings to lesser levels than when S. wuyuanensis was applied, but comparable to control treatments (no pathogen). The disease management of stem canker was also associated with significant (p < 0.05) decreases in ACC levels in royal poinciana stems when S. griseorubens was applied compared to the non-ACCD-producing S. wuyuanensis. This study is the first to report the superiority of antagonistic actinobacteria to enhance their effectiveness as BCAs not only for producing antifungal metabolites and CWDEs but also for secreting ACCD.